Observational cohort study examining apolipoprotein E status and preoperative neuropsychological performance as predictors of post-operative delirium in an older elective arthroplasty population. (5th April 2017) - Cunningham, Emma Louise; Mawhinney, Tim; Beverland, David; O'Brien, Seamus; McAuley, Daniel F; Cairns, Rebecca; Passmore, Peter; McGuinness, Bernadette
Abstract: Introduction: delirium following surgery is common and is associated with negative outcomes. Preoperative cognitive impairment has been shown to be a risk factor for post-operative delirium. Often the cognitive tests used are cumbersome. This study tests the hypothesis that the quantification of brain vulnerability, using Apolipoprotein E (ApoE) status and neuropsychological tests, both traditional and more easily administered, can quantify the risk of post-operative delirium following elective primary arthroplasty surgery. Methods: this observational cohort study recruited participants aged 65 years or older admitted prior to elective primary hip or knee arthroplasty. Baseline data was collected and participants underwent neuropsychological testing and had blood taken for ApoE genotyping preoperatively. Post-operatively participants were assessed daily for delirium using the Confusion Assessment Method (CAM) and charts were reviewed where possible for reports of delirium. Univariate and multivariate analyses of preoperative factors were undertaken to identify independent predictors of delirium. Results: between March 2012 and October 2014, 315 participants completed the study with an overall incidence of post-operative delirium of 40/315 (12.7%). Of these 18 fulfilled the CAM criteria for delirium and 22 were deemed delirious by consensus decision based on chart review. ApoE genotype was not associated with post-operative delirium in this cohort. Time taken to complete Colour Trails 2, errors in mini mental state examination and level of pain preoperatively were independent predictors of post-operative delirium. Conclusions: this study challenges the assertion that ApoE4 genotype predicts post-operative delirium. It replicates previous work suggesting cognitive impairment predicts post-operative delirium and shows for the 1st time that simple cognitive tests can be as effective as more detailed tests.